Persepsi Pengetahuan, Penghargaan Finansial, dan Pertimbangan Pasar Kerja Terhadap Minat Mahasiswa Akuntansi dalam Berkarir Menjadi Akuntan Publik - Avika Miya Olistya Depp; Setiawati, Erma (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of knowledge perception, financial rewards, and labor market considerations on accounting students’ interest in pursuing a career as a public accountant. An associative quantitative approach was used with a sample of 2021 accounting students from accredited universities in Surakarta. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that knowledge does not significantly affect students' interest, while financial rewards and labor market considerations have a significant influence. The study's limitations include a restricted sample scope and limited variables. Future research should expand the sample coverage and incorporate additional variables to obtain more comprehensive findings.